SHIFT IN THE REGIONAL BALANCE OF POWER AS A PRECONDITION FOR AZERBAIJAN’S MILITARY INTERVENTION IN NAGORNO-KARABAKH IN 2020 - Bogićević, Aleksandar; Preradović, Nikola (Srpska politička misao, 2026)
The Second Nagorno-Karabakh War of 2020 decisively influenced the regional security architecture of the South Caucasus and the fate of the protracted Azerbaijani-Armenian conflict over the status of this mountainous enclave. This paper aims to examine the circumstances that enabled Azerbaijan’s military victory and the transformation of the regional order. The theoretical framework applied is neoclassical realism, which integrates structural factors and unit-level variables in the analysis of states’ foreign policy. The paper argues that the altered regional balance of power constituted an essential precondition for Azerbaijan’s armed intervention and subsequent triumph in the autumn of 2020. This shift resulted from a combination of interrelated factors. The first pertains to Russia’s neutral stance toward the warring parties, accompanied by a gradual weakening of its regional supremacy. The second concerns the growing role of Turkey as Azerbaijan’s ally, which particularly contributed to the rapid modernisation of Baku’s armed forces. Finally, the passivity of Iran and the West, along with the deepening military cooperation between Israel and Azerbaijan, further strengthened Baku’s regional position. These factors reshaped the regional order in the South Caucasus and made Azerbaijan’s military intervention possible.